Educators' Competencies in The Qur'an Perspective - Khoyyinudin, Mohammad; Nurulloh, Khodijah Fitria (Perkumpulan Psikologi Transformasi Indonesia (P2TI), 2024)
Education is a strategic program for advancing a nation. Educators are an essential element in determining the success of the learning process. Teaching is also a profession that requires particular skills to support successful learning. One of the unique skills that educators need is competence. From an Islamic perspective, the Qur'an inspires the competence of educators. This research aims to explain educators' competence from the Al-Qur'an's perspective. This research was conducted using qualitative methods. The research approach uses literature study and tahlili. Data was obtained from the Al-Qur'an, book literature and journals. The data collected was analyzed and grouped into sub-themes descriptively. The research results show that the Al-Qur'an has provided a basis for teacher competency values. There are indicators of educational competency contained in the Al-Qur'an, according to the mufassir's opinion, consisting of knowledge, understanding, skills, values, attitudes and interests. Ultimately, there are competency values: personality competence, social competence, and professional competence. Educational entities need to pay attention to competencies to advance education in Indonesia.